The value of combined SATB2 and CDX2 detection in the differential diagnosis of colorectal adenocarcinoma - Liping Wang; Hongjun Li; Liping Feng (Medicine, 2026)
This study evaluates the diagnostic value of SATB2 and CDX2, used individually and in combination, in the immunohistochemical differential diagnosis of colorectal adenocarcinoma. A retrospective case-control diagnostic accuracy study was conducted, including 122 patients with histologically confirmed colorectal adenocarcinoma or non-colorectal adenocarcinoma. Immunohistochemical staining for SATB2 and CDX2 was performed on all cases, followed by semiquantitative interpretation. Using histopathological diagnosis as the gold standard, the diagnostic efficacy of each test index (SATB2 positive, CDX2 positive, either positive, and both positive) was calculated. SATB2 and CDX2 were highly expressed in colorectal adenocarcinoma (positive rates of 88.2% and 86.3%, respectively), which was significantly higher than in the control group (7.0% and 19.7%, P < .001). SATB2 used alone demonstrated the optimal diagnostic discrimination among single markers (AUC = 0.916, specificity 93.0%). Among the combined strategies, the “either positive” rule achieved the highest sensitivity (94.1%), whereas the “both positive” rule showed the highest specificity (98.6%) and overall discriminative ability (AUC = 0.938). PPV and NPV values were interpreted only within this case-control study population and should not be considered direct estimates of performance in populations with different disease prevalence. CDX2 showed the lowest specificity (60.0%) in differentiating gastric adenocarcinoma, whereas the “both positive” strategy maintained high diagnostic reliability across all differential scenarios. The sensitivity of both markers was significantly reduced in poorly differentiated colorectal adenocarcinoma. SATB2 is an excellent single diagnostic marker. The combined application of SATB2 and CDX2 offers complementary advantages: “either positive” is suitable for exclusion diagnosis, while “both positive” is suitable for confirmation diagnosis. This combination is an effective tool for the differential diagnosis of colorectal adenocarcinoma, although caution is needed when diagnosing poorly differentiated carcinomas.